Sarcasm on Screen: Movie Analysis of Verbal Sarcasm in Don't Look Up Movie - Cannavaro, Alfajri Ichsan (Anaphora : Journal of Language, Literary, and Cultural Studies, 2024)
This research aims to analyze the verbal sarcasm found in Don’t Look Up movie. This research also aims to discover the characters how they expressed their sarcastic utterances. The research uses a contextual pragmatic study by Leech and pragmatic structure of sarcasm by Camp. The research method is qualitative and the type of research is descriptive. The corpus of the data is the Don't Look Up movie, which was released in 2021. The technique of data collection used by watching the movie and collecting the sarcastic utterances in the transcript, sorting the data that relate to the issue, and identifying the selected data to be analyzed. The result of this research is that there are 11 sarcastic utterances that contain the types of sarcasm in Don’t Look Up movie, such as 7 propositional sarcasm, 1 lexical sarcasm, and 3 illocutionary sarcasm. Most of the data identified as propositional sarcasm because it was caused from each character in delivered and expressed their sarcasm that aims to satirize each other and also delivered by inserting some criticism in some data. Furthermore, there are 11 utterances that have an implied meaning in this research that are conveyed by the characters.